2018
DOI: 10.1007/s00894-018-3746-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new promising Plasmodium falciparum superoxide dismutase allosteric inhibitors through hierarchical pharmacophore-based virtual screening and molecular dynamics

Abstract: Malaria is the world's most widespread protozoan infection, being responsible for more than 445,000 annual deaths. Among the malaria parasites, Plasmodium falciparum is the most prevalent and lethal. In this context, the search for new antimalarial drugs is urgently needed. P. falciparum superoxide dismutase (PfSOD) is an important enzyme involved in the defense mechanism against oxidative stress. The goal of this study was to identify through hierarchical screening on pharmacophore models and molecular dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Virtual screening has effectively shortened drug development time, reduced costs and improved efficiency, which can be very useful for the development of drugs to treat diseases that do not attract the attention of pharmaceutical companies. In recent years, computer-aided drug design has been applied to the discovery of anti-parasitic drugs (Postigo et al, 2010;Dube et al, 2012;Zhao et al, 2012;Pavadai et al, 2016;Vyas et al, 2016;Kagami et al, 2017;Araujo et al, 2018). Our study also indicated that virtual screening technology could play an important role in drug discovery for the treatment of echinococcosis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Virtual screening has effectively shortened drug development time, reduced costs and improved efficiency, which can be very useful for the development of drugs to treat diseases that do not attract the attention of pharmaceutical companies. In recent years, computer-aided drug design has been applied to the discovery of anti-parasitic drugs (Postigo et al, 2010;Dube et al, 2012;Zhao et al, 2012;Pavadai et al, 2016;Vyas et al, 2016;Kagami et al, 2017;Araujo et al, 2018). Our study also indicated that virtual screening technology could play an important role in drug discovery for the treatment of echinococcosis.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, computer-aided drug design has been applied to the discovery of anti-parasitic drugs. Using pharmacophore-based virtual screening and molecular dynamics and molecular docking approaches, promising drug targets and hits are identified (Pavadai et al, 2016;Vyas et al, 2016;Kagami et al, 2017;Araujo et al, 2018). Among the predicted active compounds, some were shown to have anti-malarial activities in vitro and in vivo (Pavadai et al, 2016;Vyas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the number and permanence of hydrogen bonds in the complexes were calculated using the g_hbond module, implemented in the GROMACS 5.1.2 package and the HbMap2Grace program ( , accessed on 5 July 2021). The hydrogen bonds that showed a distance between the donor and acceptor that was lower than or equal to 3.5 Å and an angle between the donor/acceptor and the H atom that was lower than or equal to 60° were identified, as well as the bonds whose permanence time was lower than 10% of the total simulation time [ 58 ].…”
Section: Methodsmentioning
confidence: 99%